Transitioning Competency-Based Communication Assessments to the Online Platform: Examples and Student Outcomes - Sarah Scoular; Ashley Huntsberry; Toral Patel; Sara Wettergreen; Jason M. Brunner (MDPI AG, 2021)
In light of the COVID-19 pandemic, pharmacy education has shifted from in-person teaching and assessments to the virtual environment. Many education programs had previously adopted objective structured clinical examinations (OSCEs) to assess communication abilities in-person with standardized patients (SPs). However, comparative student outcome data between virtual and in-person methods as well as guidance on how to conduct communication-based OSCEs in the virtual environment is lacking. The University of Colorado Skaggs School of Pharmacy and Pharmaceutical Sciences (SSPPS) describes its methods of conducting two types of communication-based OSCEs (patient counseling and gathering a medical history). Student performance data from the two virtual OSCEs in 2020 was compared to results from two 2019 in-person OSCEs using Mann Whitney U Tests. The 2020 cohort scored significantly higher than the 2019 cohort in all variables (i.e., using effective verbal and non-verbal communication, using patient friendly education, organizing the encounter, demonstrating empathy, establishing trust, professionalism) and in overall score. However, the effect size for these findings indicate the differences between performances are generally small and more likely due to changes in grading patterns due to the pandemic.